2020
DOI: 10.1182/bloodadvances.2020001761
|View full text |Cite
|
Sign up to set email alerts
|

Flow studies on human GPVI-deficient blood under coagulating and noncoagulating conditions

Abstract: The role of glycoprotein VI (GPVI) in platelets was investigated in 3 families bearing an insertion within the GP6 gene that introduces a premature stop codon prior to the transmembrane domain, leading to expression of a truncated protein in the cytoplasm devoid of the transmembrane region. Western blotting and flow cytometry of GP6hom (homozygous) platelets confirmed loss of the full protein. The level of the Fc receptor γ-chain, which associates with GPVI in the membrane, was partially reduced, but expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“… 38 Conversely, patients with genetic deficiency in GPVI did not have significant disruption of hemostasis or other platelet activities. 39 , 40 In vivo experiments have shown that SYK deficiency or administration of the active metabolite of fostamatinib (R406) and other SYK inhibitors has a negligible effect on hemostasis. 20 , 41 Importantly, in platelet-mediated hemostasis, platelet activation and aggregation are also stimulated by thrombin, thromboxane A 2 , and ADP, which all signal through G protein-coupled receptors that are not dependent on signaling via SYK.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Conversely, patients with genetic deficiency in GPVI did not have significant disruption of hemostasis or other platelet activities. 39 , 40 In vivo experiments have shown that SYK deficiency or administration of the active metabolite of fostamatinib (R406) and other SYK inhibitors has a negligible effect on hemostasis. 20 , 41 Importantly, in platelet-mediated hemostasis, platelet activation and aggregation are also stimulated by thrombin, thromboxane A 2 , and ADP, which all signal through G protein-coupled receptors that are not dependent on signaling via SYK.…”
Section: Discussionmentioning
confidence: 99%
“…This feature makes GPVI an attractive target for the development of improved anti-platelet drugs to prevent thrombosis. Indeed, GPVI-deficient patients described so far present with no more than a minor bleeding tendency [43,47]. Interestingly, a genetic variant of GP6 was found to associate with an increased risk of venous thrombosis [48].…”
Section: Glycoprotein VI (Gpvi)mentioning
confidence: 99%
“…77 In addition, DEP-mediated activation has previously been shown to be abolished in platelets from GPVI-deficient mice. 1 Here, we expanded on this to show negatively charged DEPs (20-70 nm) and negative charged surfaces also activate human platelets through GPVI, using platelets from homozygous patients (Figure 3A), who have a mutation in the GP6 gene preventing expression 78 (see Supplementary Materials for full patient details). These patients have no GPVI expression as shown by flow cytometry and western blotting, whereas levels of other glycoprotein receptors, including CLEC-2, GPIIb/IIIa and FcγRIIA are within the normal range.…”
Section: Mechanism Of Charge Mediated Platelet Activationmentioning
confidence: 99%